Analysis Of Employee Performance Factors Through Motivation As An Intervening Variable - Fauziyanti, Wachidah; Ayunita Irawati, Marsha (Sean Institute, 2025)
This study aimed to determine the direct and indirect effects of transformational leadership and compensation on team member performance through work motivation at CV Multi Komunika Semarang. Team member performance results from the quality and quantity a team member achieves in carrying out his duties according to his responsibilities. The population in this study was 62 employees of CV Multi Komunika Semarang. The sample determination used a saturated sampling technique or census. The independent variables (Independent) in this study are transformational leadership (X1) and compensation (X2), the dependent variable is team member performance (Y), and work motivation (Z) is an intervening variable. The data collection method used a questionnaire with a data analysis method using a path analysis test with the SPSS application. This study shows that transformational leadership has a positive and significant effect on team member motivation and performance, and compensation has a positive and significant impact on team member motivation and performance. Motivation mediates the effect of transformational leadership and compensation on team member performance at CV Multi Komunika Semarang. The coefficient of determination (Adjusted R Square) is 0.847. This means that the variables of transformational leadership, compensation, and work motivation have a role of 84.7% together to explain or describe team member performance variables. At the same time, the remaining 15.3% (100% - 84.7%) is explained by other variables that affect team member performance. Through managers/leaders, the company must strive to continue to apply a transformational leadership style and develop work motivation and empowerment for employees because this influences the performance that the company's employees will achieve. The compensation provided by the company is based on team member expectations and is given relatively. Work motivation should be maintained so employees are careful, team member performance increases, and the company can achieve the desired goals.